2021
DOI: 10.1063/5.0029704
|View full text |Cite
|
Sign up to set email alerts
|

Unsteadiness characterization of shock wave/turbulent boundary layer interaction controlled by high-frequency arc plasma energy deposition

Abstract: We carried out an experimental study of Mach 2.5 airflow over a semicircular column with 15 kHz arc plasma energy deposition (APED). The APED was pulsed at microsecond time scales, and it rapidly added high-repetition-frequency thermal bubbles that propagated downstream. Time-resolved schlieren imaging with a frame rate of 30 kHz was utilized to record the dynamic flow fields. This study was aimed at investigating the effects of these thermal bubbles on the unsteadiness characterization of a shock wave/turbule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Experimental results showed that the perturbing effect of the APED on the incoming SWBLI decreased at higher flow deflection angles for the same energy deposition. Direct numerical simulations confirmed the prevention by the APED of the velocity In [52], L. Feng et al present research on the characteristics of instabilities originating during the interaction of an SW with a turbulent BL (SWBLI) which was controlled by high-frequency arc plasma energy deposition (APED) initiated by six pairs of electrodes. This study conducted experiments with Mach 2.5 airflow over a semicircular column with 15 kHz APED pulsing in the microsecond range and generating rapid, high-frequency thermal bubbles downstream.…”
Section: Filamentary Plasma: Control Of Bswesi and Swblimentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that the perturbing effect of the APED on the incoming SWBLI decreased at higher flow deflection angles for the same energy deposition. Direct numerical simulations confirmed the prevention by the APED of the velocity In [52], L. Feng et al present research on the characteristics of instabilities originating during the interaction of an SW with a turbulent BL (SWBLI) which was controlled by high-frequency arc plasma energy deposition (APED) initiated by six pairs of electrodes. This study conducted experiments with Mach 2.5 airflow over a semicircular column with 15 kHz APED pulsing in the microsecond range and generating rapid, high-frequency thermal bubbles downstream.…”
Section: Filamentary Plasma: Control Of Bswesi and Swblimentioning
confidence: 99%
“…In [52], L. Feng et al present research on the characteristics of instabilities originating during the interaction of an SW with a turbulent BL (SWBLI) which was controlled by high-frequency arc plasma energy deposition (APED) initiated by six pairs of electrodes. This study conducted experiments with Mach 2.5 airflow over a semicircular column with 15 kHz APED pulsing in the microsecond range and generating rapid, high-frequency thermal bubbles downstream.…”
Section: Filamentary Plasma: Control Of Bswesi and Swblimentioning
confidence: 99%
“…In [52], L. Feng et al present the research on characteristics of instabilities originated during the interaction of a SW with the turbulent BL (SWBLI) which was controlled by high-frequency arc plasma energy deposition (APED) initiated by six pairs of electrodes. This study conducted experiments with Mach 2.5 airflow over a semicircular column with 15 kHz APED pulsing in the microsecond range and generating rapid, high-frequency thermal bubbles downstream.…”
Section: Filamentary Plasma: Control Of Bswesi and Swblimentioning
confidence: 99%